Legal Politics DKI Jakarta Government Policies In The Implementation Of Formula-E During The Covid-19 Pandemic - Muhammad Ardhi Razaq Abqa; Faris Apriyadi; Arnanda Yusliwidaka (Universitas of Muhammadiyah Makassar, 2022)
Formula-E organizers are included in the Governor's Instruction Number 49 of 2021 and are made on a regional priority scale. This caused controversy considering that at that time, Indonesia was still hit by COVID-19, and the government was trying to handle the community and carry out economic recovery. The research problem formulation is the legal politics of the DKI Jakarta government's policy in implementing Formula-E during the covid-19 pandemic. The purpose of this research is to determine the interests of the people affected by the implementation of Formula-E, which is used as a regional priority scale in the implementation of Formula-E Instruction Governor (INGUB) Number 49 of 2021. This type of research is descriptive qualitative; namely, it describes research based on theories and legal materials about legal politics and policies made by the government. This study uses a qualitative descriptive method using literacy studies and legislation—techniques in analyzing data using narrative analysis techniques. This study concludes that the administration of government affairs must prioritize the safety of the people first above other interests. The regulations that apply must be under the hierarchy so that the existing regulations do not conflict with higher regulations because the regulations at the lower level must adapt to the regulations at the upper level, namely the 1945 Constitution (UUD 1945) and the Pancasila State Constitution.